2002
DOI: 10.1046/j.1365-201x.2002.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory action of chronic exercise on macrophage and lymphocyte cytokine production in mice

Abstract: This study was designed to evaluate the effects of 8-week voluntary running exercise on cytokine production of macrophages and lymphocytes. Seven-week-old-male BALB/c inbred mice were divided into two groups: a group given voluntary exercise (exercise group, n=32), and the other, a non-exercise group (control group, n=32). Exercise consisted of spontaneous running in wheels for 3 days per week over 8 weeks. The levels of nitric oxide (NO2-) and interleukin (IL)-1 beta production by lipopolysaccharide (LPS)-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
1
20
1
2
Order By: Relevance
“…In vivo administration of lipopolysaccharide to healthy, young, trained or untrained men revealed tissue‐specific induced inflammatory responses: Compared with their untrained counterparts, trained subjects had an enhanced lipopolysaccharide‐induced TNF‐α and IL‐6 mRNA expression in skeletal muscle and slightly reduced responses systemically and in adipose tissue 37. Some animal studies also report increases in ex vivo lipopolysaccharide‐stimulation models, with exercise training leading to increases in TNF‐α but not IL‐6 in rats38, 39 in interleukin‐1ß, interleukin‐12, TNF‐α, and interferon‐γ in mice,40, 41, 42, 43 and in TNF‐α and interferon‐ß in horses 44…”
Section: Discussionmentioning
confidence: 99%
“…In vivo administration of lipopolysaccharide to healthy, young, trained or untrained men revealed tissue‐specific induced inflammatory responses: Compared with their untrained counterparts, trained subjects had an enhanced lipopolysaccharide‐induced TNF‐α and IL‐6 mRNA expression in skeletal muscle and slightly reduced responses systemically and in adipose tissue 37. Some animal studies also report increases in ex vivo lipopolysaccharide‐stimulation models, with exercise training leading to increases in TNF‐α but not IL‐6 in rats38, 39 in interleukin‐1ß, interleukin‐12, TNF‐α, and interferon‐γ in mice,40, 41, 42, 43 and in TNF‐α and interferon‐ß in horses 44…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte proliferation is a complex event involving the participation of IL-2 and IL-2 receptor expression. IL-2 is one of the major regulatory cytokine of the immune system which can further enhance the NK cell and LAK cell growth and activity (Sugiura et al, 2002). This may further contribute to the antitumor activity of the immune cell (Wang and Johnston, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, moderate intensity exercise training enhances immune function, whereas intense exercise training depresses the immune system (27,29). With regards to the influence of endurance training on the immune function, the results of animal experiments have shown an increase in phagocytic activity and in chemotaxis of peritoneal Ms, as well as of the proliferative response of T cells to mitogens (12,14,35,36). On the other hand, few studies have evaluated the immunomodulatory effect of exercise training on peritoneal M function, since activated Ms are important sources of pro-inflammatory factors.…”
mentioning
confidence: 82%
“…The response depends on the variables of physical exercise such as intensity, volume and frequency, along with the exercise type. Several studies, however, have shown that regular moderate exercise stimulates many aspects of the immune response (27,29,33,36).…”
Section: Effects On Macrophage Functionmentioning
confidence: 99%
See 1 more Smart Citation